Implementing Halal Tourism in Mount Rinjani National Park: An Analysis of Sembalun and Torean Trekking Routes - Nadia Nuril Ferdaus; Reny Wardiningsih (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study examines the implementation of halal tourism within Mount Rinjani National Park, focusing on the Sembalun and Torean trekking routes. Using a descriptive qualitative approach, data were gathered through direct observations and interviews with local residents and tourists. Data analysis was conducted based on the Global Muslim Travel Index (GMTI) 2019 framework, categorizing needs into "need to have," "good to have," and "nice to have." Findings indicate that essential requirements (need to have), such as halal food options and worship facilities, are generally met, although some infrastructural improvements remain necessary. The good to have and nice to have categories reveal potential areas for further enhancement, particularly in providing more nuanced services aligned with Sharia principles. The study recommends bolstering infrastructure and fostering collaboration among governmental bodies, Mount Rinjani National Park management, and local communities to advance sustainable halal tourism in the region